(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The cadastral system for recording and registering rights to real estate is complex and multicomponent, focused on performing several important functions for the state: taxation, protection of private property rights, control over the use and condition of land. Practical examples show the need for a gradual reorientation of the priorities in the development of the cadastral system from the direction of accounting and registration actions towards the organization of a system of rational land use. As a research problem, the issues of developing effective mechanisms for organizing a system for the rational use of land resources and, as a result, ensuring the ecological well-being of the territory of the state are considered. The article proposes parameters whose values affect the efficiency of the cadastral system. Criteria for the optimality of the efficiency parameters of the cadastral system have been developed. The schemes of mutual influence of indicators of the effectiveness of the cadastre system and topographic and geodetic support for carrying out cadastral work, as well as the relationship of indicators of the effectiveness of the cadastre system in the implementation of a unified model of the state accounting and registration system are given.